Software engineering for resilient systems : 7th International Workshop, SERENE 2015, Paris, France, September 7-8, 2015. Proceedings /: 7th International Workshop, SERENE 2015, Paris, France, September 7-8, 2015. Proceedings. (2015) - Unknown
No abstract available